Perspectives of Differentiation Therapies of Acute Myeloid Leukemia: The Search for the Molecular Basis of Patients’ Variable Responses to 1,25-Dihydroxyvitamin D and Vitamin D Analogs - Marchwicka, Aleksandra; Cebrat, Małgorzata; Sampath, Preetha; Śnieżewski, Łukasz; Marcinkowska, Ewa (Frontiers in Oncology, 2014)
The concept of differentiation therapy of cancer is approximately 40 years old. Despite many encouraging results obtained in laboratories, both in vitro and in vivo studies, the only really successful clinical application of differentiation therapy was all-trans-retinoic acid (ATRA) based therapy of acute promyelocytic leukemia (APL). ATRA, which induces granulocytic differentiation of APL leukemic blasts, has revolutionized the therapy of this disease by converting it from a fatal to a curable one. However, ATRA does not work for other acute myeloid leukemias (AMLs). Since 1,25-dihydroxyvitamin D3 (1,25D) is capable of inducing monocytic differentiation of leukemic cells, the idea of treating other AMLs with vitamin D analogs (VDAs) was widely accepted. Also some types of solid cancers responded to in vitro applied VDAs, and hence it was postulated that VDAs can be used in many clinical applications. However, early clinical trials in which cancer patients were treated either with 1,25D or with VDAs, did not lead to conclusive results. In order to search for a molecular basis of such unpredictable responses of AML patients towards VDAs, we performed ex vivo experiments using patient’s blast cells. Experiments were also performed using 1,25D-responsive and 1,25D-non responsive cell lines, to study their mechanisms of resistance towards 1,25D-induced differentiation. We found that one of the possible reasons might be due to a very low expression level of vitamin D receptor (VDR) mRNA in resistant cells, which can be increased by exposing the cells to ATRA. Our considerations concerning the molecular mechanism behind the low VDR expression and its regulation by ATRA are reported in this paper.